Continuous separation of multiple particles by negative and positive dielectrophoresis in a modified H-filter - Lewpiriyawong, Nuttawut (2014)
The article presents a new application of the modified H-filter with insulating rectangular blocks using negative and positive DEP for separation of multiple particles in a continuous pressure-driven flow. The multiple insulating blocks fabricated along the main channel induce spatially nonuniform electric fields which exert differential repulsive (negative) or attractive (positive) DEP forces on particles, depending on the size and the polarizability of particles relative to their suspending medium. As a result, particles of different sizes and polarizability can be separated into different outlets of the H-filter. Numerical simulations are also performed to analyze the effects of block gap and width on electric field distribution and DEP force characteristics near the insulating blocks so as to provide design guidelines for optimal structural dimensions of the microfluidic device. The device performance is demonstrated by separating a three-sized particles mixture, including 2 μm fluorescent particles with an attractive DEP force and both 5 and 10 μm nonfluorescent particles with differential repulsive DEP forces. High separation rate of 99% is successfully achieved.